Adaptive responses of cardiorespiratory system and hormonal parameters to individualized high-intensity interval training using anaerobic power reserve in well-trained rowers - Wang, Xiaodong; Zhao, Liqiu (Frontiers in Physiology, 2023)
The current study investigated the efficacy of individualizing exercise intensity according to anaerobic power reserve (APR) on hormonal, physiological, and performance adaptations in athletes with different profiles. Sixteen highly-trained male rowers (age = 22 ± 3 years, height = 183 ± 6 cm, weight = 83 ± 7 kg, body fat = 11 ± 2 %, experience = 12 ± 5 years) were randomized to a high-intensity interval training consisting of 2 × (6, 6, 8, 8, 10, 10 repetitions from 1st to 6th week, respectively) × 60 s intervals using rowing ergometer at ∆%30 APR (APR∆%30) or the same sets and repetitions at 130% maximal aerobic power (MAP130%). In both groups, relief intervals were set at 1:1 with 3 min of rest between sets. On four occasions separated with 24 h recovery, participants attended the laboratory to assess 2000-m rowing ergometer performance, maximal oxygen uptake (V̇O2max) and related physiological adaptations, and hormonal parameters. Significant increases were observed in 2000-m performance, V̇O2max, ventilation at V̇O2max, first and second ventilatory threshold, MAP and maximal sprinting power (MSP), total testosterone, and testosterone to cortisol ratio in response to six weeks of APR∆%30 and MAP130% protocols. The coefficient of variation (inter-subject variability) in the adaptive response of cardiorespiratory parameters to HIIT performed using the APR∆%30 protocol was lower than those of the MAP130% group. However, this is not the case for hormonal changes. Prescribing HIIT according to the athlete’s APR normalizes mechanical and associated physiological stimulus relative to the athlete’s ceilings and causes more homogenized subsequent adaptations across athletes with different profiles. Mechanisms influencing total testosterone are multifactorial and are not affected by this approach.